The Role of Social Work in Raising Environmental Awareness of the Risks of Climate Change (Journal of the College of Education for Women, 2025)
The research discusses the role of social services in raising environmental awareness of the negative impacts of various climatic and environmental phenomena on the Earth and all its inhabitants, and seeks to enhance environmental awareness among the population by demonstrating the role of social services in reducing catastrophic environmental phenomena and working to achieve environmental sustainability. The research focuses on demonstrating the role of green social services in confronting climate change problems and maintaining environmental sustainability, while clarifying the relationship between the environment and humans in light of climate change. To work on understanding the relationship between the environment and society in light of contemporary societal changes, the researcher conducted a field study to know the real role of the social service profession in the climatic nature of society. The field aspect was represented by distributing (200) questionnaire forms in Baghdad Governorate to social specialists and environmental specialists whose opinions were discussed, and a question was raised about the role of social service in developing environmental awareness of the dangers of climate change in Iraq. The study reached many results, including that social service has a clear role in developing environmental awareness in terms of protecting it and preventing it from loss, pollution and waste, and it is one of the important roles that social specialists have begun to focus on and that it is one of the professions with close contact with humans, as the specialist deals directly with humans and the environment.